Evaluation of Rotation Effects in Steel Structures with Irregular Plan Under Earthquake in Project Management - Rezaei, Mohammad Reza (ExcelingTech, 2020)
Abstract. Because of lacking specific relationships and criteria for steel structures with bending frames and braces along with the uneven bearing system in Iranian regulations, the need to study the behavior of such structures has been considered by researchers. In this paper, with three-dimensional modeling of steel structures with six types of plans, each of which indicates a degree of asymmetry of the load-bearing system, a total of 18 models of structures under two types of linear dynamic loading and overload were studied. It is indicated that with increasing unevenness of the load-bearing system, the rotation of the structures also increases. This increase is up to 18 times more for short-term structures and up to five times more than for parallel structures than parallel structures. The discrepancy causes unexpected results. Increasing the height of the structure reduces the rotation in the diaphragm. There is no difference between the rotation of the diaphragms in terms of elastic and inelastic, while the load in the other direction of these changes for the inelastic state is sometimes up to more than 50 times the elastic state.